GREEN DEAL AND SOLAR ENERGY- PROSPECTS FOR BULGARIAN RURAL AREAS - Krum HRISTOV; Rositsa BELUHOVA-UZUNOVA; Dimo ATANASOV; Svetoslav LAVCHIEV; Georgi MRANKOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Renewable energy is essential for the European Union. The targets presented by the Green Pact are closely related to the development of renewable energy, and it has a vital role in achieving climate neutrality in the EU. Solar energy's importance has increased in the past years. It can help achieve the goals presented in the EU and contribute to the sustainable development of rural areas with unrealized potential. The aim of the study is to outline the dynamics and tendencies in solar energy development in the EU and Bulgarian energy mix and highlight perspectives in the context of rural areas. The results show challenges related to green transition in Bulgaria. Renewable energy, especially solar and wind, has increased in its role in the last few years. However, it should be noted that the country's development began from a lower starting point. Bulgaria is dependent on fossil fuels, and more than 80% of electricity is produced from coal, which is one of the substantial sources of pollution. However, some positive tendencies and possibilities exist for boosting rural economies and employment creation.